Birth of RISED - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
CTA has joined the EEC in giving financial support to an information service on information and deveIopment: RISED. Developed specially for nongovernmental organizations in the 66 ACP countries, RlSED's goal is to facilitate the circulation of...